2012
DOI: 10.1073/pnas.1116590109
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of abscisic acid activation of SLAC1 anion channel by CPK6 and OST1 kinases and branched ABI1 PP2C phosphatase action

Abstract: The plant hormone abscisic acid (ABA) is produced in response to abiotic stresses and mediates stomatal closure in response to drought via recently identified ABA receptors (pyrabactin resistance/regulatory component of ABA receptor; PYR/RCAR). SLAC1 encodes a central guard cell S-type anion channel that mediates ABA-induced stomatal closure. Coexpression of the calcium-dependent protein kinase 21 (CPK21), CPK23, or the Open Stomata 1 kinase (OST1) activates SLAC1 anion currents. However, reconstitution of ABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
427
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(459 citation statements)
references
References 60 publications
(93 reference statements)
14
427
2
1
Order By: Relevance
“…Further research on the structural basis for the HT1-OST1 interaction and phosphorylation sites on OST1 will provide a more detailed molecular mechanism underlying OST1 inhibition by HT1 kinase. Given SLAC1 is also regulated by other protein kinases including CPKs [30][31][32] and calcium sensor kinases CBL-CIPKs 52 , further work should also be conducted to find out whether HT1, similar to the PP2C A-type phosphatases in ABA signalling, can also interact with and inhibit calcium-dependent kinases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research on the structural basis for the HT1-OST1 interaction and phosphorylation sites on OST1 will provide a more detailed molecular mechanism underlying OST1 inhibition by HT1 kinase. Given SLAC1 is also regulated by other protein kinases including CPKs [30][31][32] and calcium sensor kinases CBL-CIPKs 52 , further work should also be conducted to find out whether HT1, similar to the PP2C A-type phosphatases in ABA signalling, can also interact with and inhibit calcium-dependent kinases.…”
Section: Discussionmentioning
confidence: 99%
“…A group of kinases such as OST1 (STOMATAL OPEN 1), CPKs (Ca 2 þ -dependent protein kinases) and GHR1 (GUARD CELL HYDROGEN PEROXIDE-RESISTANT 1) can phosphorylate and activate the SLAC1 anion channel 23,24,[29][30][31][32] . Such activation is often considered to be the key step for ABA-induced stomatal closure [21][22][23][24] .…”
mentioning
confidence: 99%
“…The phenotype of single gene mutants in the key SnRK2 for stomatal responses to ABA, OST1, are profound, displaying no sensitivity to ABA (Mustilli et al, 2002) or VPD (Merilo et al, 2013;Merilo et al, 2015). While other SnRK2-independent signaling pathways for ABA perception and SLAC activation have been suggested (Geiger et al, 2010;Brandt et al, 2012;Pornsiriwong et al, 2017), these are redundant and many either converge or require cross-talk with functional OST1 to activate anion channels (Brandt et al, 2015). Whether these alternative SnRK2-independent ABA signaling pathways play an adaptively relevant role in stomatal function is yet to be determined.…”
Section: Co-option Of An Ancient and Highly Conserved Aba Signaling Pmentioning
confidence: 99%
“…Structural analysis revealed that the interaction between SnRK2.6 and HAB1 mimics the interaction between ABA-bound PYL2 and HAB1 [12]. PYLs can inhibit PP2C activity in the presence of ABA, and thereby activating SnRK2.6, which can phosphorylate slow anion channel1 (SLAC1) and activate SLAC1-mediated ion currents [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In guard cells, the SnRK2s can also phosphorylate and activate the NADPH oxidase catalytic subunit RBOHF, leading to the production of reactive oxygen species (ROS) [17,22,23]. SnRK2s also interact with and phosphorylate plasma membrane anion channels such as SLAC1 to regulate ion transport [13,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%